A systematic review and meta-analysis of dementia prevalence in seven developing countries: A STRiDE project. Issue 12 (1st December 2020) - Farina, N.; Ibnidris, A.; Alladi, S.; Comas-Herrera, A.; Albanese, E.; Docrat, S.; Ferri, C. P.; Freeman, E.; Govia, I.; Jacobs, R.; Astudillo-Garcia, C.I.; Musyimi, C.; et al.
ABSTRACT: The STRiDE project sets out to support the development of effective dementia policy in middle-income countries (Brazil, India, Indonesia, Jamaica, Kenya, Mexico, and South Africa). As part of this it will generate new data about the prevalence of dementia for a subset of these countries. This study aims to identify the current estimates of dementia prevalence in these countries and where the gaps lie in the current literature. A systematic review was completed on 30th April 2019 across electronic databases, identifying dementia prevalence literature originating from any of the seven countries. Four hundred and twenty-nine records were identified following de-duplication; 28 studies met the inclusion criteria and were included in the systematic review. Pooled estimates of dementia prevalence ranged from 2% to 9% based on DSM-IV criteria; these figures were generally higher in studies using other diagnostic criteria (e.g. the 10/66 algorithm). Available prevalence data varied between countries. Only Brazil, Mexico and India had data derived from studies judged as having a low risk of bias. Irrespective of country, studies often were not explicit in detailing the representativeness of their sample, or whether there was non-response bias. Further transparent and externally valid dementia prevalence research is needed across the STRiDE countries.